Effects of different types of fruit bags on the quality of Xiahui 10 peaches - ZHANG Binbin; DU Jinhua; CHEN Hong; WANG Xiaojun; ZHANG Yuanyuan; CHEN Zheng; DING Hui; YAN Zhimei; YU Mingliang; MA Ruijuan (Guoshu xuebao)
[Objective] Fruit bagging is a common practice used by growers to improve fruit quality, prevent pest and disease infestations, avoid direct pesticide contamination, enhance edibility, improve appearance, increase commercial value and raise market competitiveness. Although additional labor and costs are incurred, fruit bagging remains as an important technical measure to ensure quality and commercial production against high temperatures and humidity in summer, frequent pest and disease outbreaks, poor coloration and low commercial quality in the middle and lower reaches of the Yangtze River region. The aim of this study was to investigate the effects of different types of fruit bags on the quality indices of Xiahui 10 peaches in order to select suitable bag types and supporting cultivation methods for improving production. [Methods] The Xiahui 10 peaches were harvested from 9-year-old trees. Peaches without bagging served as the control. Six types of fruit bags were tested: white-single-layer bags, yellow-single-layer bags, double-layer bags with yellow outside and black inside, double-layer bags with yellow outside and white inside, removable bags with black outside and white inside (removed before harvesting), and removable bags with black outside and yellow inside (removed before harvesting). Differences in the single fruit mass and other quality indices of single peaches were compared to screen suitable bag types. [Results] All types of fruit bags significantly increased the single fruit mass index, with the yellow-single-layer bags, double-layer bags with yellow outside and white inside, removable bags with black outside and white inside and removable bags with black outside and yellow inside achieving increases by14.08%, 15.04%, 13% and 17.29%, respectively, as compared to the control. The yellow-single-layer bags, double-layer bags with yellow outside and white inside, and removable bags with black outside and white inside significantly improved the fruit firmness with skin by 29.93%, 23.1% and 29.01%, respectively, while the other bags had no significant effect. The brightness value (L) of fruits protected with different bags increased from 11.64% to 57.15% as compared to the control, with the double-layer bags with yellow outside and black inside and the removable bags with black outside and yellow inside achieving the most significant effects. Additionally, the red saturation (a), color saturation (C) and red saturation/yellow saturation ratio (a/b) of the fruits were significantly lower than the control (6.8% vs 65.14%, 4.16% vs 21.3% and 8.79% vs 77.47%, respectively, p<0.05), while the yellow saturation (b) and hue angle (h) were significantly higher (6.44% vs 57.46% and 17.05% vs 143.19%, respectively, p<0.05). Furthermore, comparisons of the fruit appearance showed that different types of fruit bags lightened the red color, with the non-transparent double-layer bags with yellow outside and black inside achieving a lighter red color than the removable bags. The red appearance of fruits was improved with the use of the white-and yellow-single-layer bags as compared to the double-layer bags. The double-layer bags also reduced vividness. The white-single-layer bags, yellow-single-layer bags, removable bags with black outside and white inside, and removable bags with black outside and yellow inside increased the soluble solid content (SSC) by 2.49%, 5.72%, 7.92% and 5.65%, respectively, while the double-layer bags with yellow outside and black inside and the double-layer bags with yellow outside and white inside decreased the SSC by 7.78% and 14.16%, respectively. In addition, the SSC tended to decrease when double-layer bags were not removed before harvesting. Other than the removable bags with black outside and white inside, the bags significantly lowered the sucrose content of fruits as compared to the control (7.66% vs 15.61%, respectively, p<0.05), especially the double-layer bags with yellow outside and black inside and the double-layer bags with yellow outside and white inside. The glucose content of fruits protected with the yellow single-layer bags, removable bags with black outside and white inside, and removable bags with black outside and yellow inside was significantly higher than the control while significantly lower for fruits protected with the double-layer bags with yellow outside and white inside. The fructose content of fruits protected with white-single-layer bags and double-layer bags with yellow outside and white inside was significantly lower than the control, while significantly higher with the removable bags with black outside and white inside. Moreover, the sorbitol content of fruits protected with white single-layer bags, double-layer bags with yellow outside and black inside, and double-layer bags with yellow outside and white inside was lower than the control, while higher with the yellow-single-layer bags and removable bags with black outside and white inside. Other than the double-layer bags with yellow outside and white inside, the malic acid content of bagged fruits was lower than the control by 13.65% to 31.64%, with the removable bags with black outside and yellow inside achieving the greatest reduction. The quinic acid content of fruits protected with white-single-layer bags, yellow-black-double-layer bags, yellow-white-double-layer bags, and black-yellow-double-layer removable bags was lower than the control, while increased with the black-white-double-layer removable bags as compared to the control. The citric acid content of fruits protected with yellow-white-double-layer bags was not significantly different from the control, but significantly decreased with the other bags. Overall, the white-single-layer bags, yellow-single-layer bags, and double-layer bags with white inner lining improved the fruit quality indices. [Conclusion] Bagging can increase the single fruit mass, improve fruit appearance, and enhance or maintain firmness, taste and overall quality of Xiahui 10 peaches. Furthermore, comparisons of the effectiveness of different bag types revealed superior quality of fruits protected with white-single-layer bags, yellow-single-layer bags, double-layer bags with yellow outside and white inside, and removable bags with black outside and white inside (removed before harvesting). In the middle and lower reaches of the Yangtze River region in China, for peach cultivars that mature from early to mid-July, appropriate fruit bags can be selected based on production, market demands, and adaptation to local conditions.